PENGARUH PERHATIAN ORANG TUA TERHADAP MINAT BELAJAR SISWA SETINGKAT MADRASAH IBTIDAIYAH - Didit Darmawan; Niswatun Toyyibah (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
ABSTRACT Parental involvement and attention are important factors that support children's academic development, particularly in fostering learning interest among elementary school students. Family support, which includes assisting children during study time, providing motivation, maintaining positive communication, and supervising learning activities, can increase students’ engagement in the learning process. This study aims to examine in depth the role of parental attention in the formation and enhancement of students’ learning interest at the Madrasah Ibtidaiyah or elementary school level. The research employs a qualitative approach using a literature review method by analyzing various scientific publications relevant to the topics of parental attention and students’ learning interest. The analysis was conducted through processes of identification, classification, and interpretation of previous research findings to identify patterns in the relationship between parental attention and students’ learning interest. Students’ interest and motivation to learn can be strengthened through parental involvement, such as accompanying learning activities, providing emotional support, establishing good communication, and creating a supportive learning environment. However, students’ level of learning interest is also influenced by various other factors, including intrinsic motivation, the school learning environment, and the family’s socio-economic background. These findings indicate that parental attention is one of the external factors that plays an important role in supporting the development of students’ learning attitudes at the basic education level. This study contributes to strengthening the understanding of the importance of the family’s role as the initial educational environment in fostering students’ learning interest. ABSTRAK Keterlibatan dan perhatian yang diberikan oleh orang tua menjadi salah satu faktor yang berperan penting dalam mendukung perkembangan akademik anak, khususnya dalam menumbuhkan minat belajar pada siswa di tingkat sekolah dasar. Dukungan keluarga yang meliputi pendampingan belajar, pemberian motivasi, komunikasi yang positif, serta pengawasan terhadap kegiatan belajar dapat meningkatkan keterlibatan siswa dalam proses pembelajaran. Penelitian ini bertujuan untuk menelaah secara mendalam peran perhatian orang tua dalam proses pembentukan serta peningkatan minat belajar siswa pada tingkat Madrasah Ibtidaiyah atau sekolah dasar. Penelitian menggunakan pendekatan kualitatif dengan metode studi literatur yang menganalisis berbagai publikasi ilmiah yang relevan dengan topik perhatian orang tua dan minat belajar siswa. Analisis dilakukan melalui proses identifikasi, klasifikasi, dan interpretasi terhadap temuan penelitian sebelumnya untuk menemukan pola hubungan antara perhatian orang tua dan minat belajar siswa. Minat dan motivasi belajar siswa dapat diperkuat melalui keterlibatan orang tua, misalnya dengan mendampingi kegiatan belajar, memberikan dukungan emosional, menjalin komunikasi yang baik, serta menciptakan lingkungan belajar yang mendukung. Namun demikian, tingkat minat belajar siswa juga dipengaruhi oleh berbagai faktor lain, termasuk motivasi intrinsik, lingkungan pendidikan di sekolah, serta latar belakang sosial ekonomi keluarga. Temuan ini menunjukkan bahwa perhatian orang tua merupakan salah satu faktor eksternal yang memiliki peran penting dalam mendukung perkembangan sikap belajar siswa pada jenjang pendidikan dasar. Kajian ini memberikan kontribusi dalam memperkuat pemahaman mengenai pentingnya peran keluarga sebagai lingkungan pendidikan awal dalam menumbuhkan minat belajar siswa.